2015
DOI: 10.1016/j.clim.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies and immune biomarkers in Type 1 diabetes: A partnership for success

Abstract: The standard of care (SoC) for Type 1 diabetes (T1D) today is much the same as it was in the early 1920s, simply with more insulin options-fast-acting, slow-acting, injectable, and inhalable insulins. However, these well-tolerated treatments only manage the symptoms and complications, but do nothing to halt the underlying immune response. There is an unmet need for better treatment options for T1D that address all aspects of the disease. For decades, we have successfully treated T1D in preclinical animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 105 publications
(139 reference statements)
0
15
0
Order By: Relevance
“…However, further research is required to define reliable biomarkers for clinical use. The success of innovative immunotherapies in preventing and even reverting T1D will depend on the implementation of biomarkers of immunoregulation and regeneration that reflect therapeutic efficacy in clinical trials [45]. Some of the aforementioned biomarkers (ratio of CD4 + T cells to CD8 + T cells, IFN-γ, and IL-6) are already being used in immunointervention in human T1D such as disease prevention studies and islet transplantation and as markers of a risk of developing T1D [46].…”
Section: Collateral Damage Of the T1d Remission Phase And Newly Propomentioning
confidence: 99%
“…However, further research is required to define reliable biomarkers for clinical use. The success of innovative immunotherapies in preventing and even reverting T1D will depend on the implementation of biomarkers of immunoregulation and regeneration that reflect therapeutic efficacy in clinical trials [45]. Some of the aforementioned biomarkers (ratio of CD4 + T cells to CD8 + T cells, IFN-γ, and IL-6) are already being used in immunointervention in human T1D such as disease prevention studies and islet transplantation and as markers of a risk of developing T1D [46].…”
Section: Collateral Damage Of the T1d Remission Phase And Newly Propomentioning
confidence: 99%
“…Despite this, and given our growing appreciation regarding the complexity and heterogeneity of immune activation processes in type 1 diabetes (T1D; von Herrath et al, 2016), it appears reasonable to argue that T reg cell induction per se cannot be equated to efficacy of T1D prevention in NOD mice.In the study by Bergman et al, the application of the weak-agonistic insulin B:9-23 peptide (Stadinski et al, 2010) promotes significant disease worsening, suggesting that therapeutic application of such an approach during ongoing islet autoimmunity can be prone to undesired consequences.Given a setting prone to autoimmune activation as in T1D, one important challenge for efficient T reg cell conversion is to maintain appropriate subimmunogenic conditions, which are critically influenced by antigen dose and activation status of antigen-presenting cells and T cells (Haxhinasto et al, 2008;Sauer et al, 2008) as well as by intrinsic T cell sensitivity to antigenic stimulation. Although we agree that the selection of a 5 µg/day insulin peptide dose was a reasonable starting point to attempt T1D prevention in NOD mice, analyses of T cell-related vaccination responses (biomarkers of vaccination efficacy [Rekers et al, 2015]) would have helped to understand whether in the present experimental setup by Bergman et al (2017) the insulin therapy was indeed tolerizing. Accordingly, it has been proposed that efficient T reg cell induction requires individual optimizations of ligand dose in a given experimental environment (Kretschmer et al, 2005;Gottschalk et al, 2010) and is supported by the assessment of naive versus activated CD4 + T cells before antigen application because activated CD4 + T cells are resistant to Foxp3 + T reg cell conversion.…”
mentioning
confidence: 70%
“…Given a setting prone to autoimmune activation as in T1D, one important challenge for efficient T reg cell conversion is to maintain appropriate subimmunogenic conditions, which are critically influenced by antigen dose and activation status of antigen-presenting cells and T cells (Haxhinasto et al, 2008;Sauer et al, 2008) as well as by intrinsic T cell sensitivity to antigenic stimulation. Although we agree that the selection of a 5 µg/day insulin peptide dose was a reasonable starting point to attempt T1D prevention in NOD mice, analyses of T cell-related vaccination responses (biomarkers of vaccination efficacy [Rekers et al, 2015]) would have helped to understand whether in the present experimental setup by Bergman et al (2017) the insulin therapy was indeed tolerizing. Accordingly, it has been proposed that efficient T reg cell induction requires individual optimizations of ligand dose in a given experimental environment (Kretschmer et al, 2005;Gottschalk et al, 2010) and is supported by the assessment of naive versus activated CD4 + T cells before antigen application because activated CD4 + T cells are resistant to Foxp3 + T reg cell conversion.…”
mentioning
confidence: 81%
“…Analysis of the infiltrated lymphocytes in pancreatic islets of NOD mice with tetramers specific for insulin B9-23, IGRP 206-214 and insulin A14-20 epitopes or the relevant mimotopes [15][16][17][18][19][20][21] has shown a unique pattern in each individual mouse for the frequency of a specific CD8 1 T cell population in the islet [21]. The detection and monitoring of specific CD8 T cells may provide a valuable tool as a potential biomarker for the diagnosis and therapy of T1D [30,31]. A recent study has identified two non-overlapping human ChgA peptides that are recognized by CD8 [33], suggesting that ChgA and its epitopes could provide attractive targets for prevention and reversal of T1D through the induction of regulatory T cells [34].…”
Section: Discussionmentioning
confidence: 99%